Plant Physiology under Abiotic Stresses - Wu, Yanyou (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Abiotic stress includes not only single adversities, i.e., drought, salt, temperature, and elevated CO2, but also complex stresses, i.e., saline and alkali soil, and karst environment. Abiotic stresses strongly affect many aspects of a plant's substance and energy metabolism. Meanwhile, abiotic stress not only affects the physiological processes of photosynthesis, water metabolism, and inorganic nutrient absorption, but it also influences the electrophysiology and other physical parameters of plants. Plant physiological information, especially online physiological information, helps us to understand the plant's adaptive mechanism and take the effective measures to improve the production of horticultural plants. This Special Issue contains a collection of 11 important research works, which deepen the connotation and expand the denotation of plant physiology under abiotic stress. These works will provide a theoretical basis for the production of horticultural crops under single stresses, such as drought and salt stress, or under complex stresses, such as saline and alkali and karst environments. Readers from all over the globe are expected to greatly benefit from this Special Issue collection both in terms of their own work and to improve the productivity of horticultural crops under complex abiotic stresses. In the future, we hope that the field of plant (horticultural crop) physiology under abiotic stresses flourishes in terms of academic research and publications.